Improvement of the acoustic black hole effect by using energy transfer due to geometric nonlinearity. (September 2017) - Denis, V.; Pelat, A.; Touzé, C.; Gautier, F.
Abstract: Acoustic Black Hole effect (ABH) is a passive vibration damping technique without added mass based on flexural waves properties in thin structures with variable thickness. A common implementation is a plate edge where the thickness is locally reduced with a power law profile and covered with a viscoelastic layer. The plate displacement in the small thickness region is large and easily exceeds the plate thickness. This is the origin of geometric nonlinearity which can generate couplings between linear eigenmodes of the structure and induce energy transfer between low and high frequency regimes. This phenomenon may be used to increase the efficiency of the ABH treatment in the low frequency regime where it is usually inefficient. An experimental investigation evidenced that usual ABH implementation gives rise to measurable geometric nonlinearity and typical nonlinear phenomena. In particular, strongly nonlinear regime and wave turbulence are reported. The nonlinear ABH beam is then modeled as a von Kármán plate with variable thickness. The model is solved numerically by using a modal method combined with an energy-conserving time integration scheme. The effects of both the thickness profile and the damping layer are then investigated in order to improve the damping properties of an ABH beam. It is found that a compromise between the two effects can lead to an important gain of efficiency in the low frequency range. Abstract : Highlights: Acoustic Black Hole (ABH) effect is a passive vibration damping technique. Geometrically Nonlinear behavior is experimentally observed in beams with ABH termination. A nonlinear plate model with variable thickness is developed and numerically solved. The energy cascade observed in the strongly nonlinear regime is used for improving the low-frequency efficiency of the ABH. A balance between damping and nonlinearity is found for enhancing the performance when vibration amplitude increases.